Management Mechanisms for Synergetic Development of Tourism Industries in Uzbekistan: Mekanisme Pengelolaan untuk Pengembangan Sinergis Industri Pariwisata di Uzbekistan - Saidova Dilfuza Abdufattohovna (Academia Open, 2025)
General Background: The tourism sector is increasingly recognized as a critical component of national economic development due to its multifaceted impact on employment, infrastructure, and cultural preservation. Specific Background: In Uzbekistan, tourism reforms between 2020 and 2024 have aimed to accelerate growth through infrastructural investments, digital innovations, and policy shifts. Knowledge Gap: However, empirical studies focusing on synergistic management—particularly the integrated coordination among tourism sub-sectors—remain limited, especially in the Uzbek context. Aims: This study investigates the mechanisms and outcomes of synergistic development across hotel, transport, gastronomy, excursion, and information services in Uzbekistan’s tourism sector. Results: Using qualitative methods and statistical review, the study finds significant post-pandemic recovery in tourism revenue and infrastructure, yet highlights persistent challenges in inter-sectoral coordination, digital integration, and service standardization. Novelty: The paper introduces a contextualized model of synergistic tourism management tailored to Uzbekistan, integrating global theoretical frameworks with local empirical trends. Implications: The findings underscore the need for cohesive digital platforms, functional cluster governance, and competency-based workforce training to advance sustainable tourism and improve Uzbekistan’s global competitiveness.Higlights: Post-Pandemic Growth: Tourist arrivals in Uzbekistan surged from 1.5 million (2020) to 6.6 million (2023) due to integrated reforms. Infrastructure Expansion: Hotels, tourist companies, and transport services grew over 50%, enhancing service availability. Low Coordination: Despite growth, weak cross-sector synergy and fragmented digital systems still limit overall tourism efficiency. Keywords: Synergy, Tourism, Infrastructure, Cluster, Uzbekistan